Determination of robust solutions for the DARP with variations in transportation time. Issue 12 (2016) - Chassaing, M.; Fleury, G.; Duhamel, C.; Lacomme, P.
Abstract: The aim of this paper is to address the Dial-A-Ride Problem with stochastic transportation time between nodes. These transportation times are modeled by a Gaussian distribution. We propose a framework based on an Evolutionary Local Search to find robust solutions which can withstand variations due to the stochasticity. Our method uses a law approach to solve this problem and a simulation part to support the results. The robustness of the best known solutions published for the Deterministic Dial-a-Ride Problem on instances proposed by (Cordeau and Laporte, 2003) is first analyzed. Computational results from the Evolutionary Local Search on the Stochastic Dial-a-Ride Problem are then presented.